Evolution of the Cenozoic Tarim Basin by flexural subsidence and sediment ponding: Insights from quantitative basin modelling. (February 2020) - Li, Chao; Wang, Shengli; Naylor, Mark; Sinclair, Hugh; Wang, Liangshu
Abstract: The Tarim Basin became a closed continental sedimentary basin in the Cenozoic due to uplift of the western Kunlun, Tian Shan and the Altyn Tagh ranges in the context of the Indian-Asia collision. A north-northeast trending seismic profile across the basin reveals that Cenozoic strata comprise a wedge of sediments in the southern and northern regions generated by flexural subsidence overlain by a more uniform regional sediment drape. We obtain the subsidence profiles across the basin at 26 Ma, 13 Ma, 5 Ma and the present day using backstripping based on the sedimentary architecture shown in the seismic profile. We use a numerical finite elastic plate to model these subsidence profiles. Our modelling indicates that the southern and northern flexural depressions started to interfere to form a single flexural bulge within the basin since late Paleogene times. The flexural bulge migrated 52 km toward the western Kunlun range since 26 Ma, reflecting a decrease in the ratio of loads of the western Kunlun range versus the Tian Shan. We separate the sediment drape from the flexural subsidence according to the preceding modelling results. Our separating demonstrates that the thickness of the drape increased from 230 ± 30 m at 26 Ma to 1910 ± 200 m at present, occupying 30% of Cenozoic strata in the profile. The rise in the base level since the Paleogene is estimated as 356 ± 80 m by correcting for sediment loading of the drape. We adopt a decreasing basin width to model the evolution of the flexural subsidence, suggesting significant uplifting of the western Kunlun range and the Tian Shan from 26 Ma to 13 Ma, relative stable elevations in these ranges from 13 Ma to 5 Ma, and their rapid uplifts since 5 Ma. Highlights: The Cenozoic Tarim Basin is formed by flexure and ponding due to uplift of peripheral ranges. The southern and northern flexural depressions in the basin started to interfere since the Paleogene. The single flexural bulge within the basin migrated 52 km southward since 26 Ma. The thickness of the drape due to ponding increased from 200 to 1900 m since 26 Ma. Modelling under a decreasing basin width suggests two episodic uplifts of the ranges.